Large-Scale MIMO Secure Transmission with Finite Alphabet Inputs - Wu, Yongpeng; Wang, Jun-Bo; Wang, Jue; Schober, Robert; Xiao, Chengshan (2017)
In this paper, we investigate secure transmission over the large-scale multiple-antenna wiretap channel with finite alphabet inputs. First, we show analytically that a generalized singular value decomposition (GSVD) based design, which is optimal for Gaussian inputs, may exhibit a severe performance loss for finite alphabet inputs in the high signal-to-noise ratio (SNR) regime. In light of this, we propose a novel Per-Group-GSVD (PG-GSVD) design which can effectively compensate the performance loss caused by the GSVD design. More importantly, the computational complexity of the PG-GSVD design is by orders of magnitude lower than that of the existing design for finite alphabet inputs in Wu2012TVT while the resulting performance loss is minimal. Numerical results indicate that the proposed PG-GSVD design can be efficiently implemented in large-scale multiple-antenna systems and achieves significant performance gains compared to the GSVD design.<br
Keywords: antenna arrays; computational complexity; MIMO communication; singular value decomposition; telecommunication security; wireless channels